Expression of Human Endogenous Retrovirus-K in Spinal and Bulbar Muscular Atrophy - Rex, Cody; Nadeau, Marie-Josée; Douville, Renée; Schellenberg, Kerri (Frontiers in Neurology, 2019)
Background: Spinal and Bulbar Muscular Atrophy (SBMA) is caused by the extension of the polyglutamine tract within the androgen receptor (AR) gene, and results in a multisystem presentation, including the degeneration of lower motor neurons. The androgen receptor (AR) is known to modulate the expression of endogenous retrovirus-K (ERVK), a pathogenic viral genomic symbiont. Since ERVK is associated with motor neuron disease, such as Amyotrophic Lateral Sclerosis (ALS), we sought to determine if patients with SBMA exhibit evidence of ERVK reactivation. Results: Data from a pilot study demonstrate that peripheral blood mononuclear cell (PBMC) samples from controls and patients with SBMA were examined ex vivo for the expression of ERVK viral transcripts and proteins. No differences in ERVK RNA expression was observed between the clinical groups. In contrast, enhancement of processed ERVK Gag and integrase proteins were observed in SBMA-derived PBMC as compared to healthy control specimens. Increased ERVK protein maturation co-occurred with elevation in the expression of the pro-inflammatory transcription factor IRF1 in SBMA. Conclusions: Our findings indicate that ERVK viral protein maturation in SBMA is an unrecognized biomarker and facet of the disease. We discuss how our current understanding of ERVK-driven pathology may tie into key aspects of multi-system dysfunction in SBMA, with a focus on inflammation, proteinopathy, as well as DNA damage and repair.